2013
DOI: 10.1039/c2sc20903a
|View full text |Cite
|
Sign up to set email alerts
|

Design and preparation of new palladium precatalysts for C–C and C–N cross-coupling reactions

Abstract: A series of easily prepared, phosphine-ligated palladium precatalysts based on the 2-aminobiphenyl scaffold have been prepared. The role of the precatalyst-associated labile halide (or pseudohalide) in the formation and stability of the palladacycle has been examined. It was found that replacing the chloride in the previous version of the precatalyst with a mesylate leads to a new class of precatalysts with improved solution stability and that are readily prepared from a wider range of phosphine ligands. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
468
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 607 publications
(485 citation statements)
references
References 24 publications
12
468
0
5
Order By: Relevance
“…Treatment of 1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidene (IPr) with an aryl iodide (RC 6 H 4 I) in the presence of 0.5 mol % of [Pd 2 (dba) 3 ] (dba = dibenzylideneacetone) precatalyst affords the C2-arylated imidazolium salts {IPr-(C 6 H 4 R)}I (R = H, 4-Me, 2-Me, 4-OMe, 4-COOMe) in excellent (up to 92 %) yields. Treatment of {IPr(C 6 H 5 )}I with CuI and KN(SiMe 3 ) 2 exclusively affords the MIC-copper complexLigands play an important role in the stability and activity of metal complexes [1, 2] and, therefore, one route towards further advancements in developing efficient and robust catalysts for challenging transformations is the development of innovative promising ligand systems. Owing to strong s-donor ability and structural features N-heterocyclic carbenes (NHCs) are already recognized as privileged ligands in homogeneous catalysis.…”
mentioning
confidence: 99%
“…Treatment of 1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidene (IPr) with an aryl iodide (RC 6 H 4 I) in the presence of 0.5 mol % of [Pd 2 (dba) 3 ] (dba = dibenzylideneacetone) precatalyst affords the C2-arylated imidazolium salts {IPr-(C 6 H 4 R)}I (R = H, 4-Me, 2-Me, 4-OMe, 4-COOMe) in excellent (up to 92 %) yields. Treatment of {IPr(C 6 H 5 )}I with CuI and KN(SiMe 3 ) 2 exclusively affords the MIC-copper complexLigands play an important role in the stability and activity of metal complexes [1, 2] and, therefore, one route towards further advancements in developing efficient and robust catalysts for challenging transformations is the development of innovative promising ligand systems. Owing to strong s-donor ability and structural features N-heterocyclic carbenes (NHCs) are already recognized as privileged ligands in homogeneous catalysis.…”
mentioning
confidence: 99%
“…In general, adducts of palladacycles are far more active than the corresponding dimeric palladacycles. A number of reports have shown that phosphines adducts of palladacycles are a ective catalysts for this transformation [4,5]. As an alternative, the N-heterocyclic carbenes (NHCs) adducts of palladacycles have been proved to be excellent precatalysts [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…and its recently introduced analogues 6a and 6b [23,24] (see Scheme 3) which are readily activated by elimination of the chelating hydrocarbyl ligand. Notably, when Pd(OAc) 2 (1 mol %) was utilized as the pre-catalyst without any added supporting ligand, the model cyanation reaction did not proceed to any appreciable extent (0% conversion under the standard reaction conditions).…”
Section: Pd-catalyzed Cyanation Of Aryl Bromidesmentioning
confidence: 99%